#### Answer

$(x-6)(x+1)=0$

#### Work Step by Step

The answer is $(x-6)(x+1)=0$ since the values $x=6$ and $x=-1$ are the only ones that satisfy the equation, i.e., these values are the only solutions

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$(x-6)(x+1)=0$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.